2016
DOI: 10.2105/ajph.2016.303119
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Computerized Intervention on HIV and Intimate Partner Violence Among Substance-Using Women in Community Corrections: A Randomized Controlled Trial

Abstract: The efficacy of Computerized WORTH across multiple IPV outcomes highlights the promise of integrating computerized, self-paced IPV prevention modules in HIV prevention groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 38 publications
0
66
0
Order By: Relevance
“…Based on the information provided, facilitators identify existing ways in which women who use drugs have developed personalized coping strategies, solved problems and exhibited courage and determination [18]. Recent randomized controlled trials suggest that the programme is effective in reducing various forms of gender-based violence experienced by women who use drugs in the United States [19] and Kyrgyzstan [20], which is likely to have followon effects on HIV prevention [21]. In India, a preliminary pilot suggested that the intervention is feasible when delivered by other women who use drugs, and a pre-post evaluation indicated reductions in intimate partner and other violence victimization [22].…”
Section: Applying a Person-centred Lens To Hiv Preventionmentioning
confidence: 99%
“…Based on the information provided, facilitators identify existing ways in which women who use drugs have developed personalized coping strategies, solved problems and exhibited courage and determination [18]. Recent randomized controlled trials suggest that the programme is effective in reducing various forms of gender-based violence experienced by women who use drugs in the United States [19] and Kyrgyzstan [20], which is likely to have followon effects on HIV prevention [21]. In India, a preliminary pilot suggested that the intervention is feasible when delivered by other women who use drugs, and a pre-post evaluation indicated reductions in intimate partner and other violence victimization [22].…”
Section: Applying a Person-centred Lens To Hiv Preventionmentioning
confidence: 99%
“…Of the 1.2 million women convicted of a crime, only 15% are incarcerated; the remaining 85%, or approximately 1 million women each year, are sentenced to some form of community corrections (probation, parole, drug treatment court, alternative to incarceration) [ 13 , 15 , 16 ]. When compared with justice-involved women of other ethnicities and racial backgrounds, black women serving sentences in the community are more likely to engage in a variety of risky sexual behaviors, including having unprotected sex with paying partners, using illicit substances before and during sexual encounters, and trading sex for drugs [ 17 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intertwined with the HIV/STI epidemic among substance-using black women who are involved in the criminal justice system is the co-occurring epidemic of intimate partner violence (IPV) [ 38 40 ]. Approximately 70% of substance-using black women in the 2009 trial of the multimedia WORTH intervention reported experiencing physical, sexual, and/or injurious IPV in their lifetime [ 21 ]. Abundant research has found that experiencing IPV is strongly associated with engaging in unprotected sex, having multiple sexual partners, testing positive for HIV/STIs, and failure to access and adhere to HIV treatment [ 41 45 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Department of Health and Human Services regulations such as the Health Insurance Portability and Accountability Act Privacy Rule (Standards for Privacy of Individually Identifiable Health Information, 2016) and regulations regarding the conduct of research with human subjects (Protection of Human Subjects, 2016) have standardized and mandated data handling practice (e.g., password protection and encryption) across clinical and research institutions, limited guidance is provided on safety when using hardware, software, and Internet and wireless technology with IPV research (Bloom et al, 2014; Garabedian, Ross-Degnan, & Wharam, 2015; Gilbert et al, 2016; Glass et al, 2015; Hegarty et al, 2015; Marcano Belisario et al, 2015). A second notable gap is the lack of guidance regarding determining and responding to research participant reports of risk for suicide and/or homicide during study activities and their preferences sharing this information to providers or receiving referrals to available services.…”
mentioning
confidence: 99%